Future tourism in a robot-based economy: a perspective article. Issue 1 (12th September 2019) - Webster, Craig; Ivanov, Stanislav
Abstract : Purpose: Future tourism will take place in a robonomic economy (aka robonomics). The massive introduction of robots, artificial intelligence and automation technologies which will lead to the advent of an economy that will be qualitatively different from the current economy. The robonomic economy will have profound implications on the nature of work, level and sources of incomes, leisure time, politics, international trade and relations, ownership rights, etc., hence leading to major social, economic and political challenges and tension. The purpose of this paper is to elaborate on how tourism will be in a robonomic society. Design/methodology/approach: This is a perspective paper that shows how tourism will be in a robonomic society. This is a conceptual perspective article that shows how tourism will be in a robonomic society. Findings: This paper elaborates on the tourism/hospitality implications of robonomics, the positive and negative impacts of robonomics on tourism and vice versa. Originality/value: This is one of the first papers to discuss tourism implications of a future automated society.